The Influence of Service Quality on Train Passenger Satisfaction at Rantau Prapat Station PT KAI Persero Divre I North Sumatra - Yulianto, Depi Gusti; Awan, Awan (Railway Journal, 2024)
In order to keep clients using this kind of transportation and to keep the business afloat, PT KAI places a high priority on their satisfaction. Employees of KAI are required to utilize five dimensions in its implementation: tangibles, assurance, responsiveness, empathy, and consistency. It is undoubtedly not ideal in its implementation at each station, as some travelers continue to be dissatisfied with the offers that are made. Examples of this include the fact that some people are still unable to board the train without a ticket and the indifference of staff members. Following basic observations by the researchers, there was a decline in staff responsiveness and overall satisfaction. The goal of this study is to determine how much the independent variable affects the dependent variable. In this quantitative analysis, primary and secondary data sources are consulted. Three techniques were employed to gather data: questionnaire completion, documentation, and observation. Using SPSS (Statistical Product and Service Solution), the instrument test, classical assumption test, hypothesis test, and simple linear regression method are the data analysis techniques employed. Once the researcher had finished using the data that had been collected. With a significance value (Sig) of 0.000, it may be inferred that the quality of the services offered significantly affects passenger happiness. Less than 0.05. The T test decision-making framework indicates that H1 is accepted and H0 is rejected, indicating that service quality has an impact on passengers' pleasure with trains. When the coefficient of determination hypothesis is evaluated using the SPSS version 26 software, a value of 0.906 can be obtained. This indicates that there is a 90.6% link between passenger satisfaction and service quality, with the remaining 9.4% coming from factors that have not been thoroughly investigated.